Valproic acid silencing of ascl1b/Ascl1 results in the failure of serotonergic differentiation in a zebrafish model of fetal valproate syndrome - John Jacob; Vanessa Ribes; Steven Moore; Sean C. Constable; Noriaki Sasai; Sebastian S. Gerety; Darren J. Martin; Chris P. Sergeant; David G. Wilkinson; James Briscoe (The Company of Biologists, 2014)
Fetal valproate syndrome (FVS) is caused by in utero exposure to the drug sodium valproate. Valproate is used worldwide for the treatment of epilepsy, as a mood stabiliser and for its pain-relieving properties. In addition to birth defects, FVS is associated with an increased risk of autism spectrum disorder (ASD), which is characterised by abnormal behaviours. Valproate perturbs multiple biochemical pathways and alters gene expression through its inhibition of histone deacetylases. Which, if any, of these mechanisms is relevant to the genesis of its behavioural side effects is unclear. Neuroanatomical changes associated with FVS have been reported and, among these, altered serotonergic neuronal differentiation is a consistent finding. Altered serotonin homeostasis is also associated with autism. Here we have used a chemical-genetics approach to investigate the underlying molecular defect in a zebrafish FVS model. Valproate causes the selective failure of zebrafish central serotonin expression. It does so by downregulating the proneural gene ascl1b, an ortholog of mammalian Ascl1, which is a known determinant of serotonergic identity in the mammalian brainstem. ascl1b is sufficient to rescue serotonin expression in valproate-treated embryos. Chemical and genetic blockade of the histone deacetylase Hdac1 downregulates ascl1b, consistent with the Hdac1-mediated silencing of ascl1b expression by valproate. Moreover, tonic Notch signalling is crucial for ascl1b repression by valproate. Concomitant blockade of Notch signalling restores ascl1b expression and serotonin expression in both valproate-exposed and hdac1 mutant embryos. Together, these data provide a molecular explanation for serotonergic defects in FVS and highlight an epigenetic mechanism for genome-environment interaction in disease.